Innovation for Sustainable Development - Review of Armenia 2023 - United Nations Economic Commission for Europe (United Nations, 2023)
The UNECE Innovation for Sustainable Development Review (I4SDR) of Armenia provides a calibrated assessment and concrete recommendations for innovation policy and structural reform in the country, based on international good practices and a firm understanding of national and regional specificities. This publication focuses on an in-depth analysis of the Armenian innovation infrastructure and examines the role of the Armenian diaspora in fostering innovation-led growth. The Review is a result of an in-depth dialogue and consultation among the UNECE Secretariat, leading subject matter experts, Government officials, academia, the private sector, and other innovation stakeholders in the country.